COMPETENCE OF STUDENTS-FUTURE AIR TRAFFIC CONTROLLERS AS TO THEIR HEALTH PROTECTION IN PROFESSIONAL ACTIVITY - Оргєєва, С. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The article highlights the peculiarities of professional activity of air traffic controlles such as: professiogram, important professional skills and their importance. Main health-protecting competencies of future professional activity are defined